Calcareous nannofossil assemblage of the Smoky Hollow (SH#1) core in south central Utah - Victoria Fortiz; Rosie L Oakes; F Garrett Boudinot; Matthew M Jones; R Mark Leckie; Bradley B Sageman; Julio Sepúlveda; Timothy J Bralower (PANGAEA, 2025)
The data include nannofossil assemblages from the Cenomanian-Turonian boundary of the Smoky Hollow (SH#1) core in south central Utah. For assemblage studies, slides were made from more dilute solutions so that counts could be conducted. Nannofossil specimens were observed under a Carl Zeiss Axioskop 2 Plus light microscope at a magnification of 1000x and identified using standard taxonomy as described by Perch-Nielsen et al. (1985). Specimens one-half the size of a coccolith or larger were identified and a total of over 31,000 specimens were counted.
In: Fortiz, V et al. (2021): Trace element and calcareous nannofossil assemblage of the Smoky Hollow (SH#1) core in south central Utah [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938507